The productivity of 4th Generation KUB-2 Chicken - Tike Sartika; Sofjan Iskandar (Indonesian Center for Animal Research and Development (ICARD), 2019)
KUB-2 line of chicken has improved local chicken selected from the KUB-1 chicken line. KUB-2 was selected for more egg production and yellow shank. KUB-1 chicken has 64% various of black feather color, which sometimes tends to have unpreferred dark carcass. Yellow shank color has a positive correlation with the skin color of carcass. As many as 517 pullets of KUB-2 at 4th generation were divided into two groups of 194 pullets of KUB-2kk (yellow shank) and 323 pullets of KUB-2nk non-yellow shank). The chickens were raised intensively in the individual cages for the 24 weeks observation. Variables measured were age at first egg (AFE) bodyweight at first egg (BWFE), egg weight at first egg (EWFE), average egg weight (AEW), average egg production (AEP) during 24 weeks, feed conversion ratio (FCR) of 25-43 weeks of age, and mortality. The result showed that there was no statistically significant different (p>0.05) between KUB-2nk and KUB-2kk respectively for AFE of 156.2 d and 158.1 d, for BWFE of 1788 g and 1808 g, for EWFE of 31.32 g and 31.34 g, for AEP24 of 103.3 eggs or 61.5% and 101.9 eggs or 60.7%, and for FCR25-43 of 3.53 and 3.54. AEW increased with increasing age of hen, the mortality of the whole population was 0.98%.